Imaging appearance of severe subcapsular hepatic steatosis: mimicking hepatic embolic infarcts - H’ng, M W C (The British Institute of Radiology., 2010)
We report a case of severe subcapsular hepatic steatosis in a middle-aged woman with diabetic nephropathy requiring continuous ambulatory peritoneal dialysis (CAPD). The CT appearances of the liver were initially suspected to be due to embolic infarcts. However, an accurate diagnosis was made only after a history of intraperitoneal insulin administration was elicited, and this was confirmed on MRI with chemical shift gradient-echo pulse sequences. Haemodialysis was recommenced, and follow-up imaging 4 years later showed complete resolution of subcapsular hepatic steatosis.